Indian Classification of Cleft Lip and Palate - Balakrishnan, C. (Indian Journal of Plastic Surgery, 1975)
The common failings of conventional methods of repair of the bilateral cleft lip are briefly enumerated. Millard's two st muscle suture operation overcomes most of these shortcomings and is recommended. The basic premises on which the method is based are mentioned and the method described with the aid of diagrams.